Flavonoids from flowers of Amesiodendron chinense (Sapindaceae) - Ban, Ho Van; Van, Trinh Thi Thanh; Chien, Vu Van; Hue, Nguyen Thi; Hang, Pham Thi; Cuong, Pham Van; Tuan, Nguyen Le; Vuong, Nguyen Quoc (Vietnam Journal of Science and Technology, 2020)
From the flowers of Amensiodendron Chinese (Merr.) Hu, six known flavonoids, (-)-catechin (1), (-)-epi-catechin (2), chrysoeriol (3), quercetin-3-O-β-D-glucopyranoside (4), astragalin (5) and kaempferide-3-O-β-D-glucopyranoside (6) were isolated. Their chemical structures were elucidated by analysis of the physicochemical parameters, the NMR and mass spectral data, and comparison with those reported in the literatures.